Development of a novel indirect-expansion solar-assisted multifunctional heat pump with four heat exchangers. (July 2015) - Wang, Q; Ren, B; Zeng, ZY; He, W; Liu, YQ; Xiangguo, Xu; Chen, GM
A novel indirect-expansion solar-assisted multifunctional heat pump with four heat exchangers was proposed in this paper, which integrates a heat pump air conditioner, a solar water heater and a heat pump water heater. In addition to these three basic operation modes, it also provided five energy-saving operation modes, which resulted in a higher utilization ratio of the solar energy and lower operational cost. Experiments of the solar-assisted space heating mode, air source heat pump water heating mode and solar-assisted heat pump water heating mode have been investigated in detail at different outdoor temperatures and different water temperatures. The novel indirect-expansion solar-assisted multifunctional heat pump is especially suitable for the regions abundant in solar radiation where the space heating, space cooling and water heating are required all the year round. Practical applications : The novel IX-SAMHP can provide space cooling, space heating, hot water by one system. The space used for those appliances can be reduced effectively. Solar energy was used to assist the space heating and water heating and defrost process and it can save the energy consumption efficiently.